KEBIJAKAN PEMERINTAH INDONESIA DALAM MENYIKAPI TINDAKAN PENYADAPAN OLEH AUSTRALIA - Saputra, Dodi; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is motivated by the intercepts made by Australia against the president, first lady, and other Indonesian official. This research aims to describe the strategic partnership and the ups and downs of diplomatic relations between the two countries, and to explain the intercepst made by Australia against of Indonesia then to explain the Indonesian Government’s policy against the intercepts case,This research uses qualitative research methods. Research conducted by way of explaining based on existing data. Then techniques used in this research libraries from various sources such as books, journals,newspapers and also the documentation is accessible fro the internet. The theory used in this research is the theory of the rational actor models of decisiom making and the concept of foreign policy. In this model Graham T. Allison mentioned that in decision making abroad is described as a process of intellectual selection based on top of existing alternatives.This result in the research was the government’s policy towards Indonesia by interceps actions Australia is recalled its ambassador from Australia, stopping a number of cooperation with Australia, and for the continuation of cooperation between government of Indonesia and Australia drew up a code of conduct.Keywords : Policy, Decision Making, intercepts, Diplomatic Relations